Applying the bronchopulmonary dysplasia framework to necrotizing enterocolitis - O’Connell, Amy E. (Frontiers in Pediatrics, 2024)
Necrotizing enterocolitis (NEC) is a devastating disease of the neonatal intestine, causing widespread intestinal necrosis as well systemic illness that frequently results in death. Because the clinical onset of NEC is sudden and difficult to predict, NEC is considered an acute event. However, NEC does not occur in utero, meaning that postnatal exposures are required, and it does not typically occur right after birth, suggesting that longitudinal changes may be occurring before NEC can develop. In this perspective, the author considers whether NEC should be re-considered as a problem of disordered intestinal epithelial development, with required maladaptation over time prior to the onset of the necrotic event. This framework is similar to how bronchopulmonary dysplasia is currently conceptualized. They also advocate that NEC researchers incorporate this possibility into future studies on NEC susceptibility and pathogenesis. Department of Pediatrics, and the Harvard Digestive Disease Center (P30DK034854-36).